Postoperative hypoparathyroidism after thyroid operation and exploration of permanent hypoparathyroidism evaluation - Wang, Xi; Wang, Shun-lan; Cao, Yang; Li, Chun-qiao; He, Weiping; Guo, Zhu-ming (Frontiers in Endocrinology, 2023)
Background: To investigate the risk factors for hypoparathyroidism, discuss the prevention of postoperative hypoparathyroidism and explore the permanent postoperative hypoparathyroidism evaluation (PPHE). Methods: A total of 2,903 patients with thyroid nodules were treated between October 2012 and August 2015. Serum calcium and intact parathyroid hormone (iPTH) levels were measured at 1 day, 1 month, and 6 months postoperatively. The incidence and management of hypoparathyroidism were analyzed. The PPHE was established on the risk factors and clinical practice. Results: A total of 637(21.94%) patients developed hypoparathyroidism, and 92.15% of them had malignant nodules. The incidence rates of transient and permanent hypoparathyroidism were 11.47% and 10.47% respectively. The iPTH level was lower in patients with malignant nodules and underwent total thyroidectomy (TT) and central-compartment neck dissection (CND). These factors were independently associated with the recovery rate of parathyroid function. The score for PPHE={iPTH}+{sCa}+{surgical procedure}+{reoperation}+{pathologic type}. The scoring system was developed and we distribute the score for low, middle and high risk of permanent postoperative hypoparathyroidism as 4-6, 7-9 and 10-13, respectively. The differences of the recovery rates of parathyroid function in several risk groups were statistically significant (P<0.001). Conclusion: Simultaneous TT and CND is a risk factor for hypoparathyroidism. The reoperation is not associated with hypoparathyroidism. Identification of parathyroid glands in situ and preservation of their vascu¬lar pedicles are key factors in managing hypoparathyroidism. The PPHE can forecast the risk of permanent postoperative hypoparathyroidism well.